Genes responsible for proliferation, differentiation, and junction adhesion are significantly up-regulated in human ovarian granulosa cells during a long-term primary in vitro culture - Kranc, Wiesława; Brązert, Maciej; Budna, Joanna; Celichowski, Piotr; Bryja, Artur; Nawrocki, Mariusz J; Ożegowska, Katarzyna; Jankowski, Maurycy; Chermuła, Błażej; Dyszkiewicz-Konwińska, Marta; Jeseta, Michal; Pawelczyk, Leszek; et al. (Histochemistry and cell biology, 2019)
The human ovarian granulosa cells (GCs) surround the oocyte and form the proper architecture of the ovarian follicle. The ability of GCs to proliferate and differentiate in the conditions of in vitro culture has been proven. However, there is still a large field for extensive investigation of molecular basics, as well as marker genes, responsible for these processes. This study aimed to find the new marker genes, encoding proteins that regulate human GCs in vitro capability for proliferation and differentiation during long-term primary culture. The human follicular GCs were collected from hyper-stimulated ovarian follicles during IVF procedures and transferred to a long-term in vitro culture. The culture lasted for 30 days, with RNA samples isolated at days 1, 7, 15, 30. Transcriptomic analysis was then performed with the use of Affymetrix microarray. Obtained results were then subjected to bioinformatical evaluation and sorting. After subjecting the datasets to KEGG analysis, three differentially expressed ontology groups "cell differentiation" (GO:0030154), "cell proliferation" (GO:0008283) and "cell-cell junction organization" (GO:0045216) were chosen for further investigation. All three of those ontology groups are involved in human GCs' in vitro lifespan, proliferation potential, and survival capability. Changes in expression of genes of interest belonging to the chosen GOs were validated with the use of RT-qPCR. In this manuscript, we suggest that VCL, PARVA, FZD2, NCS1, and COL5A1 may be recognized as new markers of GC in vitro differentiation, while KAT2B may be a new marker of their proliferation. Additionally, SKI, GLI2, FERMT2, and CDH2 could also be involved in GC in vitro proliferation and differentiation processes. We demonstrated that, in long-term in vitro culture, GCs exhibit markers that suggest their ability to differentiate into different cells types. Therefore, the higher expression profile of these genes may also be associated with the induction of cellular differentiation processes that take place beyond the long-term primary in vitro culture.
Keywords: Up-Regulation; lidé; ženské pohlaví; buněčná diferenciace; buněčná adheze; mladiství; Cell Differentiation; folikulární buňky; proliferace buněk; Adolescent; Granulosa Cells; Female; Young Adult; Cell Proliferation; Adult; adhezní spoje; Cell Adhesion; Adherens Junctions; ovarium; kultivované buňky; Cells, Cultured; Humans; dospělí; mladý dospělý; upregulace; Ovary